Penguatan Branding UMKM melalui Implementasi Program Mahasiswa KKN UINSU di Desa Saribu Raja Janji Maria - Cindy Antika; Nikmah Amalia Harahap; Puja Maharani Pasaribu; Yustia Dewi; Zuhrinal M. Nawawi (Pusat Riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises play a strategic role in supporting rural economies; however, many of them continue to face limitations in branding management, which affects their product competitiveness. This condition indicates that the challenges encountered by these enterprises are not merely technical in nature but also related to limited strategic understanding in building business identity. This study aims to examine the role of the Community Service Program implemented by students of Universitas Islam Negeri Sumatera Utara in strengthening the branding of Micro, Small, and Medium Enterprises in Saribu Raja Janji Maria Village, Toba Regency. The study employed a qualitative approach using a participatory community service method, involving enterprise owners, students, and village stakeholders. Data were collected through in-depth interviews, participant observation, and activity documentation, and subsequently analyzed using thematic analysis. The findings reveal that prior to the mentoring program, branding was predominantly perceived as a visual element. Through student involvement, this perception shifted toward a more structured business strategy, encompassing the development of business identity, product differentiation, and the utilization of digital media. Students functioned as strategic resources by facilitating knowledge transfer and enhancing the contextual capacity of enterprise owners. The study concludes that the Community Service Program contributes meaningfully to strengthening enterprise branding and supports inclusive rural economic development, while emphasizing the importance of sustained institutional support to ensure the long-term impact of the program.